PENGARUH JENIS FILTER BERBEDA TERHADAP PERTUMBUHAN DAN KELULUSHIDUPAN IKAN NILA MERAH (Oreochromis niloticus) PADA MEDIA PEMELIHARAAN AIR PAYAU SISTEM RESIRKULASI - Yudhani Prasetyo; Mulyadi Mulyadi; Niken Ayu Pamukas (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was carried out on March 1 to May 10 2018 which was held at the Regional Technical Implementation Unit (UPTD) of Bengkalis located on Jl. MariamanTeluk Papal Village, Bantan District, Bengkalis Regency, Riau Province.This study aims to obtain the best filter substrate in increasing growth and survival of red tilapia (Oreochromisniloticus) seeds which are maintained in brackish water with a recirculation system. The method used in this study is an experimental method using a single-factor completely randomized design (RAL) with four treatment levels and three replications. The treatment applied is P0 = Gravel, palm fiber, sand, P1 = Zeolite, palm fiber, sand, P2 = charcoal, palm fiber, sand and P3 = bioball, palm fiber, sand. The parameters measured in this study include water quality, absolute weight growth, absolute length growth, specific growth rate (SGR) and survival rate (SR). The best treatment was obtained in P3 treatment (bioball, palm fiber and sand) giving the results of water quality, namely temperature 28,1 – 30,3 0C, pH 7,4 – 8,1, DO 5,24 – 6,53 mg / L, NH3 0,06 – 0,40 mg / L, NO2 0,056 – 0,90 mg / L and NO3- 0,28 – 0,190 mg / L, the absolute weight of red tilapia is 10,12 g, the absolute length is 4,99 g, specific growth rate of 6,63% and survival of 93,33%.Keywords : Resirculation system, filter, red tilapia (Oreochromis niloticus)